AlGaN/GaN HEMT-based high-sensitive NO2 gas sensors. (28th May 2019) - Ranjan, Akhil; Agrawal, Manvi; Radhakrishnan, K.; Dharmarasu, Nethaji
Abstract: We report on a Pt/AlGaN/GaN HEMT-based gas sensor with interdigitated electrodes for NO2 sensing over the temperature range of 30 °C–300 °C. The sensors show a change in current (Δ I ) of 0.5 mA with sensitivity of 1.2% for 10 ppm NO2 at 30 °C and recovers at elevated temperature. The sensitivity increases with the increase in relative humidity (0 to 90%) at 30 °C. High sensitivity of 5.5% with a corresponding Δ I of 1.8 mA is achieved for 10 ppm NO2 concentration at 300 °C, which is higher than the reported value under similar measurement conditions. The large surface area of the interdigitated electrodes and the catalytic property of the platinum functionalization layer enables high sensitivity for low NO2 concentrations of <10 ppm.